Analisis Manajemen Risiko Pengelolaan Zakat pada Lazismu Al-Mukhlisin - Maulida; Rakhmawati, Aneta (Indonesian Journal of Applied Accounting and Finance, 2025)
The existence of zakat institutions is very helpful and makes it easier for muzaki to fulfill and distribute zakat funds effectively. However, in its implementation, zakat institutions also face various challenges, including risks that can hinder institutional performance and the achievement of goals. Lazismu Al-Mukhlisin is known to not have a special guideline regarding zakat management risk. This study aims to determine how zakat management risk is implemented in Lazismu Al-Mukhlisin and what risks occur in the institution. This type of research is qualitative with a descriptive approach. This study used data collection techniques in the form of observation, interviews, questionnaires, and documentation. The results show that Lazismu Al-Mukhlisin has 4 different levels of risk. The risks that occurred consist of 7 types and 20 detailed risks. At the low level, 4 risks were identified, meaning the risks did not need to be considered because the impact was small. At the medium level, 4 risks were identified, and at this level the risks were acceptable but needed to be managed. At the high level, 8 risks were identified, and these risks should be avoided and require attention from senior management. At the extreme level, 4 risks were identified, and at this level the risks cannot be tolerated and require immediate action.